THE INVESTIGATION OF THE FRACTURITY OF COMPLICATED RESERVOIR AND THE ESTIMATION OF THEIR INFLUENCE ON THE FILTRATION CHARACTERISTICS - BEZRODNA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of quantitative of an estimation filtration properties of the crack reservoir are given on the basis of definition of structure its pore space by well-logging date on an example of water-saturated and oil-saturated horizons of the oil-well of Dnipro-Donetsk depression.